Pengurusan sumber perikanan secara 'Co-management': Kajian kes di Kedah dan Perlis / Jamal Ali and Ahmad Mahdzan Ayob - Ali, Jamal; Ayob, Ahmad Mahdzan (URDC UiTM Perlis & UPENA, 2005)
The purpose of this paper was to examine the factors affecting compliance behavior with regard to zoning regulation among trawler, purse seine and drift net fishermen in three fishing areas of Kedah and Perlis. Frequent violations of regulation will impact on the demand for protection, and therefore lead to greater expenditure on law enforcement. Policy makers who want to improve compliance face two choices: the first choice is whether to focus only on building staff capacity to detect and correct non-compliance, or the second choice a combination of strategies building staff capacity and at the same time building commitment among fishermen so that they will comply with regulations. The results of the empirical analysis provided evidence of the relationship between co-management strategies on the one hand, and types of fishermen on the other.